Sex differentiation in the European eel: histological analysis of the effects of sex steroids on the gonad - COLOMBO, Giuseppe; GRANDI, Gilberto (Journal of Fish Biology, 1995)
The effects of sex steroids on sex differentiation in the European eel were studied. The steroids, 17α-methyltestosterone (MT) and 17α-ethynylestradiol (EE), were given in the diet to 6-8 cm elvers and to 15-18 cm and 22-25 cm yellow eels. In our rearing conditions a very large percentage of the untreated eels developed as males. No masculinizing effect of MT could be demonstrated. The EE, administered at a dose of 10 mg kg-1 of diet to 6-8 cm elvers and 15-18 cm eels, induced ovarian differentiation in about 90 and 65% of eels respectively, while in the control <5% of females was recorded. In 22-25 cm yellow eels a moderated feminizing effect was observed. Histological analysis of the gonads of treated eels showed that sex steroids affect the gonadal structure. The androgen stimulates hypertrophy of compact connective tissue, early differentiation of Leydig cells, Sertoli cells and early formation of the spermatic duct. Oestrogen inhibits the differentiation of these structural components and stimulates the differentiation of follicular cells and an ovarian structure. The involvement of gonadal structural components is discussed in relation to the effect of steroid treatment and to the peculiarities of sex differentiation in the European eel